1991
DOI: 10.1111/j.1600-0897.1991.tb01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recurrent Aborters by Immunization With Paternal Cells—Controlled Trial

Abstract: A paired sequential trial was undertaken to establish whether paternal mononuclear cells improved the prognosis in couples with recurrent abortions. For this purpose, 10(7)-10(8) cells obtained from the blood of partners were injected intravenously, subcutaneously, and intra-dermally into women who had had three or more consecutive miscarriages with the same partner. Control women were given normal saline, injected in the same manner. The result of the sequential analysis showed that there was no significant b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 8 publications
0
52
0
1
Order By: Relevance
“…A very good review and commentary on the problems with conclusions as to whether LI can reduce the risk of another SAB in patients with RSAs has been provided by Clark and Daya [29], The study by Cauchi et al [3], which did not support the positive data of Mowbray et al [30], failed to use an adequate number of lymphocytes [31] nor did they give two thirds of the dose of lymphocytes intra venously; similarly, the study by Ho et al [13] failed to use two thirds of the dose intravenously and did not speci fy cell concentration as elaborated by Clark and Daya [29], Furthermore, in the study ofH oet al [13], there was a reduction in SABs (38 vs. 21%) in those given LI vs. those receiving maternal lymphocytes. Yet, these were two of the four studies used for the meta-analysis by Fra ser et al [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very good review and commentary on the problems with conclusions as to whether LI can reduce the risk of another SAB in patients with RSAs has been provided by Clark and Daya [29], The study by Cauchi et al [3], which did not support the positive data of Mowbray et al [30], failed to use an adequate number of lymphocytes [31] nor did they give two thirds of the dose of lymphocytes intra venously; similarly, the study by Ho et al [13] failed to use two thirds of the dose intravenously and did not speci fy cell concentration as elaborated by Clark and Daya [29], Furthermore, in the study ofH oet al [13], there was a reduction in SABs (38 vs. 21%) in those given LI vs. those receiving maternal lymphocytes. Yet, these were two of the four studies used for the meta-analysis by Fra ser et al [15].…”
Section: Discussionmentioning
confidence: 99%
“…The latter groups jus tify their conclusions based on various studies demon strating benefits of the following placebo therapies for RSA: cerclage [1]; infusion of trophoblast membrane vesi Received: August 29, 1994 Accepted: October 25, 1994 cles without eliciting an immune response [2]; saline [3], or psychotherapy [4], Though there have been several studies demonstrating a benefit to LI [5][6][7][8][9][10][11][12], only the study by Mowbray [5] had randomized controls. However, subsequently, three other controlled studies concluded that LI was not effective in preventing SABs [3,13,14]. In fact, a recent meta-analy sis concluded that 'we do not believe that the current evi dence supports any benefit of immunotherapy' and that 'fair evidence exists against its use' [15].…”
Section: Introductionmentioning
confidence: 99%
“…The successful pregnancy rate was 82% for the whole group and 86% for the subgroup of primary aborters. Intravenous immunoglobulin use in unexplained abortions was termed 'passive immunization', as opposed to 'active immunization' with allogenic lymphocytes which was introduced in 1981 and has been used widely throughout the world (Mowbray et al, 1985;Cauchi et al, 1991;Ho et al, 1991;Gatenby et al, 1993). Because passive immunization has no adverse effects and resultant pregnancy rates are similar to active immunization with paternal lymphocytes, this mode of treatment seems more advantageous.…”
Section: Intravenous Immunoglobulin Use In Unexplained Recurrent Abormentioning
confidence: 99%
“…Immunotherapy for women with recurrent abortions by allogenic leukocytes was introduced in 1981, and has been the © European Society for Human Reproduction and Embryology subject of controversy, although widely practised, throughout the world (Mowbray et aL, 1985;Cauchi et aL, 1991;Ho et aL, 1991;Gatenby et aL, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…To dale, only one placebo-controlled double-blind trial [6| has reported a benefieial elTeet from immunolherapy, but this trial has been criticised forthe small number of palients studied (49 couples), and more importantly for the much lower than expected success rate among ihe control group. Two more recent reports [7,8] have shown no statistical benefit from immunotherapy. There are several on-going multi-centre trials of alki-immuiii/alion for unexplained RSA, and we have participated in one such study.…”
Section: Introductionmentioning
confidence: 99%